2008
DOI: 10.1016/j.cub.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric Chromatin Is Organized into an Intramolecular Loop in Mitosis

Abstract: The C loop conformation reveals the structural basis for sister-kinetochore clustering in budding yeast and for kinetochore biorientation and thus resolves the paradox of maximal interstrand separation in regions of highest cohesin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
243
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(257 citation statements)
references
References 40 publications
14
243
0
Order By: Relevance
“…However, similar to other eukaryotes, cohesin is enriched within a 20-to 50-kb domain around centromeres (Blat and Kleckner 1999;Glynn et al 2004;Weber et al 2004). Strikingly, the pericentric cohesins in budding yeast appear to be arranged as a cyclindrical array around the spindle (Yeh et al 2008), which may be due to the formation of an intramolecular C loop on each sister chromatid that extends 25 kb (Yeh et al 2008). Cohesin would therefore encircle a single chromatid rather than sisters in this region, resolving the apparent "cohesin" paradox where the highest levels of cohesin reside in the areas that are physically split at metaphase.…”
Section: The Centromerementioning
confidence: 83%
“…However, similar to other eukaryotes, cohesin is enriched within a 20-to 50-kb domain around centromeres (Blat and Kleckner 1999;Glynn et al 2004;Weber et al 2004). Strikingly, the pericentric cohesins in budding yeast appear to be arranged as a cyclindrical array around the spindle (Yeh et al 2008), which may be due to the formation of an intramolecular C loop on each sister chromatid that extends 25 kb (Yeh et al 2008). Cohesin would therefore encircle a single chromatid rather than sisters in this region, resolving the apparent "cohesin" paradox where the highest levels of cohesin reside in the areas that are physically split at metaphase.…”
Section: The Centromerementioning
confidence: 83%
“…A recent immunoelectron microscopy study confirmed that CENP-A occupies the outer third of the centromeric chromatin (13). An alternative looping model has been suggested for the point centromere of budding yeast (14).…”
mentioning
confidence: 93%
“…Centromere and kinetochore tension and stretch are important for maintaining chromosome alignment (McIntosh et al, 2002), stabilizing kinetochore microtubule (kMT) attachments (Nicklas and Koch, 1969), spindle checkpoint signaling (Musacchio and Salmon, 2007;McEwen and Dong, 2009), and also for the back-to-back orientation of sister kinetochores (Loncarek et al, 2007). At least three independent factors have roles in the establishment of centromeric tension in metaphase: sister chromatid cohesion (Yeh et al, 2008), the elastic properties of chromatin (Houchmandzadeh et al, 1997;Almagro et al, 2004;Marko, 2008), and the higher order structure of the centromeric chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Centromere and kinetochore tension and stretch are important for maintaining chromosome alignment (McIntosh et al, 2002), stabilizing kinetochore microtubule (kMT) attachments (Nicklas and Koch, 1969), spindle checkpoint signaling (Musacchio and Salmon, 2007;McEwen and Dong, 2009), and also for the back-to-back orientation of sister kinetochores (Loncarek et al, 2007). At least three independent factors have roles in the establishment of centromeric tension in metaphase: sister chromatid cohesion (Yeh et al, 2008), the elastic properties of chromatin (Houchmandzadeh et al, 1997;Almagro et al, 2004;Marko, 2008), and the higher order structure of the centromeric chromatin.Condensin is important for the architecture of mitotic chromosome arms (Coelho et al, 2003;Hudson et al, 2003;Hirota et al, 2004;Hirano, 2006), but it also localizes to centromeres (Saitoh et al, 1994;Gerlich et al, 2006), where condensin I, but not condensin II was reported to have a role in stabilizing the structure (Gerlich et al, 2006). It has recently been suggested that condensin could have a role in regulating the elastic behavior of centromeric chromatin.…”
mentioning
confidence: 99%